Analysis of Lifestyle and Consumption Behavior on Purchase Intentions for Beledang Fish Chips at Ommey Mandiri Bengkulu - Pio Rahmat Saputra; Herri Fariadi; Rika Dwi Yulihartika (Utami Publisher, 2026)
The rising economic value of beledang fish in the local food industry and for export calls for a deep understanding of the dynamics of modern consumer preferences, which are becoming increasingly selective when it comes to purchasing traditional snacks in the Bengkulu City area. This study aims to analyze the lifestyle of Beledang fish chip consumers, analyze the consumption behavior of Beledang fish chips at Ommey Mandiri Bengkulu, and analyze the influence of lifestyle and consumption behavior on the purchase interest in Beledang fish chips at Ommey Mandiri Bengkulu. The research method used was a quantitative approach employing a survey technique with a questionnaire and multiple linear regression. The results revealed that the lifestyle level was 29.42, falling into the high category, and the consumption behavior level was 28.07, also in the high category. Lifestyle (X1) and consumption behavior (X2) influence the purchase intention for Beledang fish chips. The Lifestyle variable (X1) has a calculated t-value of 2.708 with a p-value of 0.010, while the Consumption Behavior variable (X2) has a calculated t-value of 3.819 with a p-value of 0.001. The critical t-value of 1.687 at the 0.05 significance level indicates that the calculated t-values for the Lifestyle and Consumption Behavior variables are greater than the critical t-value; therefore, these independent variables have a significant effect on the dependent variable, namely Purchase Intention.